1998
DOI: 10.1007/s004210050366
|View full text |Cite
|
Sign up to set email alerts
|

Electron spin resonance spectroscopic detection of oxygen-centred radicals in human serum following exhaustive exercise

Abstract: Free radicals or oxidants are continuously produced in the body as a consequence of normal energy metabolism. The concentration of free radicals, together with lipid peroxidation, increases in some tissues as a physiological response to exercise - they have also been implicated in a variety of pathologies. The biochemical measurement of free radicals has relied in the main on the indirect assay of oxidative stress by-products. This study presents the first use of electron spin resonance (ESR) spectroscopy in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
96
0
20

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(125 citation statements)
references
References 24 publications
9
96
0
20
Order By: Relevance
“…This, in combination with the positive association between Δ PBN-adduct and Δ LOOH, strongly suggests that the free radicals detected in the present investigation were lipid-derived. This is in agreement with the work of Ashton et al [31], who also observed a positive correlation between LOOH and PBN adduct concentration at rest (r=0.80, p<0.05) and immediately following exercise using an exercise paradigm identical to that employed in the present study (r=0.71, p<0.05). We suggest that the metal-catalysed reductive decomposition of LOOH may be the precursor of the compound formation of EPR-detectable spin-trapped lipidderived alkoxyl radicals (LOOH±Fe 2+ =RO·).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This, in combination with the positive association between Δ PBN-adduct and Δ LOOH, strongly suggests that the free radicals detected in the present investigation were lipid-derived. This is in agreement with the work of Ashton et al [31], who also observed a positive correlation between LOOH and PBN adduct concentration at rest (r=0.80, p<0.05) and immediately following exercise using an exercise paradigm identical to that employed in the present study (r=0.71, p<0.05). We suggest that the metal-catalysed reductive decomposition of LOOH may be the precursor of the compound formation of EPR-detectable spin-trapped lipidderived alkoxyl radicals (LOOH±Fe 2+ =RO·).…”
Section: Discussionsupporting
confidence: 94%
“…It is also feasible that ascorbic acid acted intracellularly as well as in the blood, since cells are saturated at doses of 200 mg [41]. It has been suggested that ascorbic acid is most effective at the aqueous-lipid interface of the cell membrane, scavenging intracellular aqueous radicals [31].…”
Section: Discussionmentioning
confidence: 99%
“…Marked increases in the amplitude of a spin-trapped radical were seen to coincide with coronary reperfusion. Similar data have also recently been reported from studies of human subjects undertaking strenuous exercise protocols (Ashton et al 1998).…”
Section: Spin Trappingsupporting
confidence: 86%
“…There are several reports indicating increased oxidative stress and decreased antioxidant levels during exercise 11,15,[48][49] . The hydroperoxide levels were measured using FOX-1 assay and levels were found in a normal range 27 .…”
Section: Table5mentioning
confidence: 99%